Improving Production System Performance by Approaching Problem Solving Procedures for Components in Advanced Technology Manufacturing - Aksöz, Lucy; Saarelainen, Amanda (My University, 2018)
In advanced technology manufacturing such as in the security and defence industry, complex endproducts are built from expensive components for which high quality levels are essential. The concept of Lean production and its practices has for decades supported companies in their development of quality focused products. Solving problems related to the components of a product is a daily task performed at the case company. Today, this problem solving is carried without any standards or guidelines. Therefore, the purpose of this thesis is to identify how problem solving procedures in advanced technology manufacturing – used for resolving component problems in the production flow – can apply Lean practices as a means to increase the production system performance. Performance in this context refers to improvement of the production rate of the products. The expected outcome is a standard for how to resolve problems related to components in the production of advanced technology. The suggested procedure and its standard were developed through a case study followed by analysis of quantitative and qualitative data using value stream mapping. The purpose was fulfilled by assessing application of Lean practices in currently used problem solving procedures and this assessment was used as a foundation for the procedure. The procedure includes two separate parts that are intertwining and covers both short-and long-term solutions to a identified problem. The procedure is an example of how Lean practices can be applied in administrative and creative processes. The theoretical contribution is application of Lean practices and methods in administrative and creative processes in an organisation with complex products and high quality demands. The practical contribution is a standard for how to resolve component problems in advanced technology manufacturing as a means to improve the production system performance. Further research will be to investigate if the suggested problem solving procedure can be used in other environments, such as high volume production, as well as see how technology trends, e.g. Internet of Things and Industry 4.0, affects the problem solving procedures.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics